Pericardial hyperechogenicity and "comets" in patients with acute pericarditis but no pericardial effusion: a comparison study with age-matched healthy controls - Sartorio, Daniele; Siniscalchi, Carmine; Reverberi, Claudio; Gaibazzi, Nicola (Acta bio-medica de l'Ateneo Parmense, 2016)
According to the published data and guidelines the diagnosis of pericarditis is mainly clinical; if we exclude patients with pericardial effusion, no single study has been able to relate specific echocardiographic findings to acute pericarditis. We hypothesized that pericardial hyperechogenicity and a defined finding that we named "pericardial comets", in analogy to lung comets, may be associated with acute pericarditis. We retrospectively analysed the echocardiograms of patients aged <50 y/o with a confirmed pericarditis diagnosis and compared them with 2 prospectively healthy controls groups (either < or > 50 y/o) to detect a potential association of pericardial hyperechogenicity and/or pericardial comets with acute pericarditis. Comparison between the pericarditis and the control groups did not evidence significant differences regarding the prevalence of hyperechogenicity and pericardial comets when comparing patients with pericarditis and age-matched controls (younger than 50 years); the group of elderly healthy controls (>50 y/o) showed significantly lower prevalence of pericardial hyperechogenicity (p<0.001) and comets (p<0.001), compared with the other 2 groups. A significantly higher number of patients with pericarditis demonstrated ≥2 pericardial comets compared with age-matched controls (68% vs 48%, p=0.042). The echocardiographic prevalence of both pericardial hyperechogenicity and comets per patient is heavily influenced by age (inversely proportional), but the presence of at least 2 pericardial comets is significantly more frequent in patients with pericarditis than in healthy aged-matched controls. Nonetheless, this echocardiographic finding may have limited clinical usefulness, due to the frequent detection of ≥2 comets in healthy young subjects also.